User-preferred position of computer displays: effects of display size. - Shin G; Hegde S; Shin, Gwanseob; Hegde, Sudeep (Human Factors, 2010)
Objective: Effects of display size and dual display setting on preferred display and keyboard positions were evaluated.Background: User-preferred display position may vary as its size changes or when multiple displays are used. It is also not known whether the use of larger displays or multiple displays would influence positioning of the keyboard.Method: Participants (N=19) who had normal visual acuity (20/30 or better) determined preferred positions of the display and the keyboard during a data entry task in four display setups (19, 24, 27.5, and dual 19 in.). The size of capital characters (3.2 mm high) was kept consistent between setups.Results: Preferred viewing distance ranged from 0.68 m (19-in. display) to 0.76 m (27.5-in. display). No significant differences in viewing distance and display height were found between the single 19-in. display and dual 19-in. displays setups. The preferred position of the keyboard was consistent between display setups.Conclusion: Participants placed larger displays farther and lower while maintaining the display top at or near eye height. Preferred position of the dual displays in landscape setting did not differ from that of a single display. It appears that the preferred display position varies with the vertical dimension of the overall viewable area of the display.Application: The results of this study can be used to determine the dimensions or adjustability of computer workstations for larger displays or multiple displays settings.